Optimized Enzymatic Synthesis of Hesperidin Fatty Acid Esters in a Two-Phase System Containing Ionic Liquid - Yollanda Edwirges Moreira Franco; Alexandra C.H. Frankland Sawaya; Thiago Grando Alberto; Patrícia de Oliveira Carvalho; Natália Dalfré; Fabiano Jares Contesini; Maria Elisa Melo Branco de Araújo (Molecules, 2011)
Response surface methodology (RSM) based on a five-level, three-variable central composite design (CCD) was employed for modeling and optimizing the conversion yield of the enzymatic acylation of hesperidin with decanoic acid using immobilized Candida antarctica lipase B (CALB) in a two-phase system containing [bmim]BF4. The three variables studied (molar ratio of hesperidin to decanoic acid, [bmim]BF4/acetone ratio and lipase concentration) significantly affected the conversion yield of acylated hesperidin derivative. Verification experiments confirmed the validity of the predicted model. The lipase showed higher conversion degree in a two-phase system using [bmim]BF4 and acetone compared to that in pure acetone. Under the optimal reaction conditions carried out in a single-step biocatalytic process when the water content was kept lower than 200 ppm, the maximum acylation yield was 53.6%.